Cystine/Glutamine Mixture Supplementation Attenuated Fatigue during Endurance Exercise in Healthy Young Men by Enhancing Fatty Acid Utilization - Sihui Ma; Miho Ono; Ami Mizugaki; Hiroyuki Kato; Masashi Miyashita; Katsuhiko Suzuki (MDPI AG, 2022)
Exercise-induced fatigue is a multi-origin physical and mental phenomenon. Efforts to diminish the above predisposition may contribute to endurance, along with athletic well-being, while development of nutritional strategies to optimize condition and exercise performance are essential issues for athletes and trainers. Dietary amino acids are being discussed for their specific health-promoting properties beyond their role as building blocks of proteins. Glutamine, along with cysteine, are two kinds of amino acids that are reported extensively for their anti-oxidation, anti-inflammation, and immune-regulation properties, and are promising in sport applications. In the present study, we designed a randomized, placebo-controlled, crossover trial to examine effects of 7-day supplementation of cystine/glutamine mixture (Cys2/Gln) on self-reporting fatigue index (ratings of perceived exertion, RPE), energy metabolism, and inflammation. We also employed a C2C12 myotube model to examine the capacity of cystine for fatty acid utilization. Cys2/Gln supplementation alleviated fatigue by decreasing RPE and enhanced fatty acid oxidation during a 60 min endurance exercise in human trials, while cystine increased fatty acid utilization in C2C12 myotubes by enhancing mitochondrial respiration. In summary, Cys2/Gln supplementation exerts positive effects on ameliorating exercise-induced fatigue, mechanisms of which can be attributed to enhancement of fatty acid utilization.